El ruido: reciente respuesta legal y jurisprudencial - Martín-retortillo Baquer, Lorenzo (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
This paper analyses the recent case-law of the Spanish Constitutional Court (Tribunal Constitucional) and of the European Court of Human Rights regarding the responsibility of the State related to noise pollution.